Pengembangan LKPD Berbasis STEM pada Materi Usaha dan Energi untuk Meningkatkan Kemampuan Pemecahan Masalah Peserta Didik di SMP Negeri 5 Banjarmasin - Aulia Hasanah; Yasmine Khairunnisa; Rizky Febriyani Putri (CV.ITTC INDONESIA, 2025)
Students face obstacles in solving problems or problems related to learning materials, especially materials related to calculations, especially in science learning. Based on this, this research is aimed at making LKPD with a STEM approach in learning effort and energy material that is in accordance with the validity, practicality, and effectiveness assessment indicators so that it is designed to improve students' ability to solve problems. The method applied is the R&D approach with stages adapted to the ADDIE model. The trial implementation was applied to 30 students in class VIII E at SMP Negeri 5 Banjarmasin. Data collection techniques involved LKPD validation instruments, learner response questionnaires, and cognitive tests to measure problem solving skills. The results of the study showed the following: (1) the validity level of STEM-based LKPD products obtained a value of 0.76 which was declared valid, (2) the practicality value of 72.08% showed a practical level, and (3) the effectiveness obtained a value of 0.62 which met the effective category. Based on the results of the study, STEM-based LKPD on effort and energy can be applied in learning activities.